Machine Learning Prediction of Stress-Induced D-dimer Reactivity in Male Physicians with and without Burnout - von Känel, Roland; Gronemeyer, Marie; Zuccarella-Hackl, Claudia; Holzgang, Sarah A.; Sivakumar, Sinthujan; Pazhenkottil, Aju P.; Gomez Vieito, Diego; Princip, Mary (Seminars in Thrombosis and Hemostasis, 2025)
Acute emotional stress can trigger acute coronary syndrome (ACS), potentially via hypercoagulable states. Circulating D-dimer is an established marker of fibrin turnover and stress-related coagulation activation, yet predictors of D-dimer stress reactivity remain unclear, especially in high-risk groups such as male physicians with burnout. We examined predictors of D-dimer changes during acute stress and recovery in 60 male physicians with and without burnout. Participants underwent the Trier Social Stress Test, with D-dimer and other biomarkers assessed across four time points over 1 hour. The area under the curve (AUC) for D-dimer was calculated to capture overall reactivity. We applied the least absolute shrinkage and selection operator (LASSO) regression to identify relevant predictors among demographic, behavioral, psychosocial, and physiological variables, followed by traditional linear regression to estimate effect sizes. LASSO regression identified five key predictors of D-dimer stress reactivity: Prestress D-dimer, habitual alcohol consumption, prestress cortisol, stress-induced epinephrine (EPI) surge, and adverse childhood experiences (ACEs). In linear regression, all but prestress cortisol remained significant independent predictors, collectively explaining 50.4% of the variance in D-dimer AUC. Specifically, higher alcohol consumption (ΔR2 = 0.117, p < 0.001), larger EPI surge (ΔR2 = 0.081, p = 0.003), and more ACEs (ΔR2 = 0.044, p = 0.026) were associated with heightened D-dimer responses, while higher prestress D-dimer was associated with attenuated reactivity (ΔR2 = 0.208, p < 0.001). Our findings highlight the role of early adversity, alcohol consumption, and sympathoadrenal activation in stress-induced coagulation activation, as reflected by D-dimer reactivity. If validated, these predictors may help identify individuals at elevated risk for stress-triggered ACS and inform targeted prevention strategies.
Keywords: hypercoagulability; D-dimer; psychology; cardiology; atherothrombosis; thrombosis